APPLICATION OF THE HYPOGYMNIA PHYSODES LICHEN AS AN ACCUMULATIVE BIOINDICATOR OF ANTHROPOGENIC ATMOSPHERE POLLUTION - T. A. Trifonova; A. S. Salmin (Юг России: экология, развитие, 2019)
Aim. This study was aimed at assessing the possibility of using the Hypogymnia physodes (L.) Nyl. lichen as an accumulative bioindicator of atmospheric air pollution in industrial cities.Methods. Under the conditions of aerial anthropogenic pollution in the city of Kazan, bulk concentrations of such heavy metals (HM) as Pb, Cr, Fe, Cu, Co and Ni were determined in the thalli of epiphytic H. physodes lichen using X‐ray fluorescence analysis.Results. According to the data obtained, the samples of lichen thalli contained 0.02÷3.08, 0.68÷2.82, 6.46÷542.99, 6,28÷21,52, 0.01÷0.32 and 0.03÷1.48 mg/kg of lead, chromium, iron, copper, cobalt and nickel, respectively.Conclusion. It is established that the city districts characterized by different envi‐ ronmental conditions showed various HM contents in lichen thalli. On the basis of the elemental composition of the thalli, zoning of the city area was carried out.  In addition to instrumental methods, a centile analysis revealed high HM concentrations in the lichen thalli. The conducted research has confirmed high biomonitoring characteristics of the H. physodes lichen.